An octupolar bis(porphyrinato) terbium(iii) complex with the highest off-resonant hyperpolarizability. Issue 37 (25th April 2017) - Sun, Junshan; Han, Yinfeng
Abstract : A novel bis(porphyrinato) terbium double-decker complex HTb(DADAPor)2 with the octupolar molecular exhibits the large off-resonant first hyperpolarizability. Abstract : A novel bis(porphyrinato) terbium double-decker complex HTb(DADAPor)2 with a twisted cuboid octupolar molecular symmetry exhibits the largest off-resonant first hyperpolarizability, as evaluated by harmonic light scattering measurements with = 1700 × 10 −30 esu.